VARIASI SIFAT FISIKA KAYU KETAPANG (Terminalia catappa) PADA ARAH AKSIAL DAN RADIAL - Herianto Herianto (Agrienvi: Jurnal Ilmu Pertanian, 2018)
This research proves the variation of Ketapang Wood Physical Characteristics on fresh water content, air dry water content, specific gravity, shrinkage and development due to differences in the location of wood along the stem. The study used a completely randomized design (CRD) with 3 replications. The research standard used DIN as a sample taken as many as 3 pieces each part of the stem so that the number of test samples on one tree as many as 99 test samples for each treatment. The treatments examined by axial direction of the stem in the section of Base (P), Middle (T), Edge (U) and further tests using the smallest real difference test (BNT). Results of the study The physical properties of ketapang wood in general have an average fresh water content (73.04%), air dry water content (47.76%). Maximum density (0.47), Development of dry to maximum kiln conditions (5.94%), development of maximum dry air to dry conditions (2.45%). Ratio (T / R) at maximum conditions to air dryness (1.45%) including low classification. Ratio (T / R) of maximum conditions to kiln dry (1.56%).